Religious Moderation Policy Implementation in the Structure of the Merdeka Curriculum in Senior High Schools: Study in Public and Private Senior High Schools - Sahudi Sahudi; Mukhsin Mukhsin; Yayat Hidayatulloh; Ani Rindiani; Ilzam Hubby Dzikrillah Alfani (LPPM Institut Agama Islam Diniyyah Pekanbaru, 2025)
Abstract This study analyzes the implementation of the religious moderation policy within the Merdeka Curriculum in senior high schools, focusing on a comparison between Public and Private Senior High Schools. Using a qualitative approach with a multiple-case study design, data were collected through in-depth interviews, participatory observation, and document analysis at two schools in Bandung City. The findings reveal significant variations in implementation strategies between the two types of schools. The Public Senior High School employed a structural-formal approach through the development of project modules and integration into curriculum instruments, while the Private Senior High School adopted a cultural-contextual approach through supplements to religious education materials and the habituation of values. This contrast highlights the context-dependent nature of policy translation, where institutional identity significantly shapes the implementation pathway. Key determinants of successful implementation included visionary leadership, teacher capacity, and support from the school ecosystem, with the main challenges being administrative burden, limited resources, and social pressures. This study concludes that the effectiveness of implementing the religious moderation policy heavily depends on seach each school's ability to develop strategies aligned with its institutional characteristics and socio-cultural context. The research implications emphasize the importance of flexible and differentiated policy approaches, as well as strengthening school capacity to adapt the national curriculum according to the specific conditions of each educational unit. Keywords: Merdeka Curriculum, Multiple-Case Study, Policy Implementation, Religious Moderation, Secondary Education Abstrak Studi ini menganalisis implementasi kebijakan moderasi agama dalam Kurikulum Merdeka di sekolah menengah atas, dengan fokus pada perbandingan antara Sekolah Menengah Atas Negeri dan Swasta. Menggunakan pendekatan kualitatif dengan desain studi kasus multi, data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan analisis dokumen di dua sekolah di Kota Bandung. Temuan menunjukkan variasi signifikan dalam strategi implementasi antara kedua jenis sekolah. Sekolah Menengah Atas Negeri menerapkan pendekatan struktural-formal melalui pengembangan modul proyek dan integrasi ke dalam instrumen kurikulum, sementara Sekolah Menengah Atas Swasta mengadopsi pendekatan kultural-kontekstual melalui penambahan materi pendidikan agama dan pembiasaan nilai-nilai. Kontras ini menyoroti sifat penerjemahan kebijakan yang tergantung konteks, di mana identitas institusional secara signifikan membentuk jalur implementasi. Faktor penentu keberhasilan implementasi meliputi kepemimpinan visioner, kapasitas guru, dan dukungan dari ekosistem sekolah, dengan tantangan utama berupa beban administratif, sumber daya terbatas, dan tekanan sosial. Studi ini menyimpulkan bahwa efektivitas implementasi kebijakan moderasi agama sangat bergantung pada kemampuan masing-masing sekolah untuk mengembangkan strategi yang selaras dengan karakteristik institusional dan konteks sosio-budaya mereka. Implikasi penelitian ini menekankan pentingnya pendekatan kebijakan yang fleksibel dan terdiferensiasi, serta penguatan kapasitas sekolah untuk menyesuaikan kurikulum nasional sesuai dengan kondisi spesifik masing-masing lembaga pendidikan. Kata kunci: Kurikulum Merdeka, Moderasasi Agama, Pelaksanaan Kebijakan, Pendidikan Menengah, Studi Kasus Multi